Automaticity A Theoretical and Conceptual Analysis. [article]. - Moors, Agnes
Several theoretical vies of automaticity are discussed. Most of these suggest that automaticity should be diagnosed by looking at the presence of the features such as unintentional, uncontrolled/uncontrollable, goal independent autonomous purely stimulus driven, unconscious , efficient and fast. Contemporary views furhter suggest that these features should be investigated separately. The authors examine whether features of automacity can be disentangled on a conceptual level, because only then is the separate investigation of them worth the effort. They conclude that the conceptual analysis of features is to a large extent feasible. Not all researchers agree with this position, however. The authors show that assumptions of overlap among features are determined by the other researchers' views of automaticity and by the models they endorse for information processing in general. -- (from the author)
Keywords: Automatic; Unintentional; Uncontrolled; Autonomous; Unconscious